Про оптимізацію класичну та системну - Yatskevich, V. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2008)
The disadvantages of the theory of classic optimization are considered in comparison with the theory of system optimization. Pictures of optimization are specified.